Unraveling taste enhancement mechanism of yeast-inoculated reduced-salt fermented sausage: Proteolysis, taste compound formation, and receptor binding of potential salty/salty taste-enhancing peptides - Dewei Huang; Gaoxin Feng; Iftikhar Hussain Badar; Bayierta Bayinbate; Junhan Fan; Baocai Xu; Linwei Yang; Qianqian Yu; Yingying Hu; Lang Zhang (Food Microbiology, 2026)

Study on pig cough recognition and spatial localization based on multi-source noise separation - Yue Cao; Zhe Yin; Yongpeng Duan; Penghui Li; Jing Zeng; Linwei Li; Guangying Hu; Zhenyu Liu (Computers and Electronics in Agriculture, 2026)

Cosmic spike removal based on multi-feature fusion for long-time integrated Raman spectral detection - Huijie Wang; Xu Liu; Xujin Hu; Wenhui Sun; Shuang Xiong; Jinjin Wu; Linwei Shang; Jianhua Yin (Analytica Chimica Acta, 2026)

Turncoat? Native Nitrogen‐Fixing Legumes Facilitate Plant Invasion via Soil Microbes and Nitrogen Transfer - Zhenwei Xu; Warwick J. Allen; Linwei Wu; Menglong Liu; Yi Hu; Jingfeng Wang; Mingyan Li; Xiao Guo; Weihua Guo (Global Change Biology, 2026)
Nitrogen deposition often promotes plant invasions and can arise from multiple sources. However, it remains unclear whether native legumes facilitate invasive plants directly through biotic nitrogen transfer or indirectly via soil microbial mediation. It is also unknown how exogenous nitrogen addition influences these facilitative effects. To address these questions, we combined evidence from a greenhouse experiment and global meta‐analysis. The greenhouse experiment tested the effects of neighboring plants (a native nitrogen‐fixing legume Albizia julibrissin ; a native non‐nitrogen‐fixing legume Styphnolobium japonicum ; or a conspecific) on the growth of invasive Rhus typhina and its native congener R. chinensis . Within‐pot membrane treatments were used to obstruct microbial and nitrogen movement between focal and neighboring plants, with and without added nitrogen. The total biomass of invasive R. typhina increased when grown with the nitrogen‐fixing legume compared with conspecific neighbors, but not when grown with the non‐nitrogen‐fixing legume. Positive effects of the nitrogen‐fixing legume on R. typhina were suppressed when nitrogen transfer or soil microbial movement was obstructed by membranes. Exogenous nitrogen addition did not alter the growth of invasive R. typhina or its interactions with legumes. The biomass of native R. chinensis did not differ among neighboring plant treatments, indicating that facilitation by legumes favored the invasive species. The global meta‐analysis of 268 effect sizes from 46 studies of the effects of legumes on neighboring plants also revealed that native legumes enhanced invasive plants' performance. Together, our findings recognize nitrogen‐fixing legumes as overlooked facilitators of plant invasion, operating through both nutrient and microbial mediated pathways. These findings highlight a paradox in which native species can act as “turncoats,” accelerating invasion and reshaping plant communities under global change.

Two key triggers and their mechanisms of the spring rainy season onset over southern China - Kexu Zhu; Wen Chen; Peng Hu; Linwei Jiang; Ruowen Yang; Lixuan Huang; Qingyu Cai; Yongmao Peng; Jingnan Li; Lu Gao; Qi Yan; Yehong Luo (Atmospheric Research, 2026)

A cytokine receptor domeless restrains mud crab reovirus infection via JAK-STAT signaling pathway in mud crab (Scylla paramamosain) - Hengwei Deng; Yetong Ke; Shaoping Weng; Lei Hu; Wenfeng Zhang; Yujia Sun; Linwei Yang; Xuewen Wang; Mingyang Feng; Weiliang Guo; Zhihong Zhong; Dongdong Zhang; et al. (Fish & Shellfish Immunology, 2025)

Odor and taste characteristics, transduction mechanism, and perceptual interaction in fermented foods: a review - Yingying Hu; Iftikhar Hussain Badar; Lang Zhang; Linwei Yang; Baocai Xu (Critical Reviews in Food Science and Nutrition, 2025)

Observational climatology and interannual variability of the spring rainy season onset over southern China: Objective definition and influence from tropical Pacific Ocean - Kexu Zhu; Wen Chen; Peng Hu; Yehong Luo; Ruowen Yang; Linwei Jiang; Qingyu Cai; Lu Gao; Jingnan Li; Yongmao Peng; Changhao Wu; Ziqi Niu (Atmospheric Research, 2025)

Advancements in production, assessment, and food applications of salty and saltiness-enhancing peptides: A review - Yingying Hu; Iftikhar Hussain Badar; Yue Liu; Yuan Zhu; Linwei Yang; Baohua Kong; Baocai Xu (Food Chemistry, 2024)

Increased FGL1 Expression Predicts Poor Prognosis and Promotes EMT in Head and Neck Squamous Cell Carcinoma - Zhiyong Pan; Weiqun Hu; Jinqiao Huang; Zhicong Zheng; Enrun Lin; PingPing Wang; Linwei Mao (Biochemical Genetics, 2024)

Mystery of bisphenol F-induced nonalcoholic fatty liver disease-like changes: Roles of Drp1-mediated abnormal mitochondrial fission in lipid droplet deposition - Linwei Zhang; Xuexue Xie; Jingxian Tao; Sizhe Wang; Miaoyang Hu; Xi Wang; Zheng Yu; Liuting Xu; Yuxin Lin; Weilan Wu; Jie Cheng; Linlin Wu; et al. (Science of The Total Environment, 2023)

Characterization of aquifer heterogeneity by tomographic slug test responses considering wellbore effects - Quan Liu; Linwei Hu; Rui Hu; Ralf Brauchler; Yixuan Xing; Junjie Qi; Thomas Ptak (Journal of Hydrology, 2023)

A large-scale climate-aware satellite image dataset for domain adaptive land-cover semantic segmentation - Songlin Liu; Linwei Chen; Li Zhang; Jun Hu; Ying Fu (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Cross-well multilevel pumping tests – A novel approach for characterizing the changes of hydraulic properties during gas storage in shallow aquifers - Linwei Hu; Maike Schnackenberg; Götz Hornbruch; Klas Lüders; Wolf Tilmann Pfeiffer; Ulrike Werban; Sebastian Bauer (Journal of Hydrology, 2023)

Mapping conduits in two-dimensional heterogeneous karst aquifers using hydraulic tomography - Xintong Wang; Xiang-Zhao Kong; Linwei Hu; Zhenhao Xu (Journal of Hydrology, 2023)

Ionizing radiation exposure: hazards, prevention, and biomarker screening - Hongxiang Mu; Jing Sun; Linwei Li; Jie Yin; Nan Hu; Weichao Zhao; Dexin Ding; Lan Yi (Environmental Science and Pollution Research, 2018)

Evaluating the lingering effect of livestock grazing on functional potentials of microbial communities in Tibetan grassland soils - Mengmeng Wang; Shiping Wang; Linwei Wu; Depeng Xu; Qiaoyan Lin; Yigang Hu; Xiangzhen Li; Jizhong Zhou; Yunfeng Yang (Plant and Soil, 2016)

Proteomics analysis of liver tissues from C57BL/6J mice receiving low-dose 137Cs radiation - Lan Yi; Linwei Li; Jie Yin; Nan Hu; Guangyue Li; Dexin Ding (Environmental Science and Pollution Research, 2016)

Responses of the functional structure of soil microbial community to livestock grazing in the T ibetan alpine grassland - Yunfeng Yang; Linwei Wu; Qiaoyan Lin; Mengting Yuan; Depeng Xu; Hao Yu; Yigang Hu; Jichuang Duan; Xiangzhen Li; Zhili He; Kai Xue; Joy van Nostrand; et al. (Global Change Biology, 2013)
Microbes play key roles in various biogeochemical processes, including carbon (C) and nitrogen (N) cycling. However, changes of microbial community at the functional gene level by livestock grazing, which is a global land‐use activity, remain unclear. Here we use a functional gene array, GeoChip 4.0, to examine the effects of free livestock grazing on the microbial community at an experimental site of T ibet, a region known to be very sensitive to anthropogenic perturbation and global warming. Our results showed that grazing changed microbial community functional structure, in addition to aboveground vegetation and soil geochemical properties. Further statistical tests showed that microbial community functional structures were closely correlated with environmental variables, and variations in microbial community functional structures were mainly controlled by aboveground vegetation, soil C/N ratio, and NH 4 + ‐N . In‐depth examination of N cycling genes showed that abundances of N mineralization and nitrification genes were increased at grazed sites, but denitrification and N‐reduction genes were decreased, suggesting that functional potentials of relevant bioprocesses were changed. Meanwhile, abundances of genes involved in methane cycling, C fixation, and degradation were decreased, which might be caused by vegetation removal and hence decrease in litter accumulation at grazed sites. In contrast, abundances of virulence, stress, and antibiotics resistance genes were increased because of the presence of livestock. In conclusion, these results indicated that soil microbial community functional structure was very sensitive to the impact of livestock grazing and revealed microbial functional potentials in regulating soil N and C cycling, supporting the necessity to include microbial components in evaluating the consequence of land‐use and/or climate changes.

Bestimmung von hydraulischen Parametern in Lockergesteinen: Ein Vergleich unterschiedlicher Feldmethoden - Ralf Brauchler; Rui Hu; Linwei Hu; Thomas Ptak (Grundwasser, 2012)